Developing Digital Book Based on Lafran Pane' Thought for Increasing State Defend Attitude of Students - Umi Azizah; Djono Djono; Akhmad Arif Musadad (Program Studi Pendidikan Sejarah FKIP Universitas Mulawarman, 2020)
In the globalization era, technology development grows rapidly. The development of technology accompanied with the decreasing of states defend attitude among Indonesian. This phenomenon evidenced by development of life that has been influenced by foreign culture, of sectarian solidarity, individualism, primordial, and the moral degradation of Indonesian which can threaten the integration of the nation. Education has an important role to deal with these problems. Teachers must be able to find instructional innovations that can be used to improve state defend attitude of students, because very important for future of the nation. Instructional innovation can be used by revive characters which it contains the values of state defend in the form of digital books. Lafran Pane is one of the Indonesian heroes who have thoughts about an intellectual's attitude towards the progress of the nation and state, especially students. Lafran Pane emphasized that student must be able to love their homeland, be hold on their beliefs, reform of thought in all fields, create harmony between religions, and be aware of their obligations as a fighter to elevate national dignity. Lafran Pane’s thought contain the values of state defense and moral can be integrated in education. This paper aims to provide learning innovations to improve state defend attitude of students.